2022
DOI: 10.3390/molecules27185794
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Extraction of Flavonoids from Potentilla fruticosa L. Using Natural Deep Eutectic Solvents

Abstract: A series of natural deep eutectic solvents (NADESs) were prepared with choline chloride, betaine, and a variety of natural organic acids in order to find new environmentally-friendly green solvents to replace the traditional solvents. The NADESs were employed to extract flavonoids from Potentilla fruticosa L. (PFL) with the help of ultrasound. The eutectic solvent diluted with an appropriate amount of water improved the extraction ability of flavonoids due to the decrease of solution viscosity. The microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This result is aligned with the fact that bark is known to have a higher native concentration of polyphenols [ 3 ]. Overall, data suggest that DESs mixtures are an interesting alternative to traditional chemical solvents for the extraction of polyphenols [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result is aligned with the fact that bark is known to have a higher native concentration of polyphenols [ 3 ]. Overall, data suggest that DESs mixtures are an interesting alternative to traditional chemical solvents for the extraction of polyphenols [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extraction efficiency of the DES-based UAE method is due to cavitation bubbles in the DESs, and the ultrasonic wave passage produces damage in the plant cell wall, causing the release of cell content into the medium, which significantly accelerates the extraction process, decreasing extraction time, and increases extraction yield of flavonoids [81]. Xue et al prepared eight NADESs to extract flavonoids from PFL with the UAE method, and the optimal extraction conditions (40:1 mL/g of solvent/solid ratio, 318 W of ultrasonic power, and 47 min of extraction time) were found with the maximum extraction yield, providing an example on the use of NADES for replacing traditional solvents and enabling efficient extraction [82]. It was found that the extraction ability of NADESs was significantly higher than that of traditional solvents, and the DES solution broke the cell structure more effectively and promoted the extraction solution to break through the barrier of the cell walls with the help of ultrasound.…”
Section: Uae Of Flavonoids Using Dessmentioning
confidence: 99%
“…They have very good antioxidative and antimicrobial properties, which makes them promising natural preservatives. Examples of flavonoid extraction with DESs from plant material are presented in Table . ,,,,,,, …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%